Peran Badan Pertanahan Nasional (BPN) sebagai Mediator dalam Penyelesaian Sengketa Pertanahan - Ach. Fadlail; Maria Ulfa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
and the results of managed land, whether land in the form of agricultural land, plantations or homestead land as a place to live. However, to date, problems related to land continue to occur and in fact the number continues to increase, starting from ownership rights, cultivation rights, control rights and land issues that arise due to dual ownership where both have certificates for the land. The National Land Agency (BPN) is an institution that was specifically formed to resolve land issues in Indonesia with the hope that people will have legal certainty and legal force over the land they own so that it does not cause new problems in people's lives. By using normative juridical research, the results of this research found that BPN has a central role in realizing certainty, justice and benefits for land managed by the community. So BPN plays an important role in solving land problems and at the same time providing solutions to the problems above. The conclusion of this research is that making BPN a mediator in land disputes before they go to the legal realm is the best solution to obtain legal certainty and resolution of land disputes experienced by the community.